The molecular gas environment in the 20 km s -1 cloud in the central molecular zone - Lu, Xing; Kruijssen, Diederik (The astrophysical journal, 2017)
We recently reported a population of protostellar candidates in the 20 km s −1 cloud in the Central Molecular Zone of the Milky Way, traced by H 2 O masers in gravitationally bound dense cores. In this paper, we report molecular line studies with high angular resolution (∼3″) of the environment of star formation in this cloud. Maps of various molecular line transitions as well as the continuum at 1.3 mm are obtained using the Submillimeter Array. Five NH 3 inversion lines and the 1.3 cm continuum are observed with the Karl G. Jansky Very Large Array. The interferometric observations are complemented with single-dish data. We find that the CH 3 OH, SO, and HNCO lines, which are usually shock tracers, are better correlated spatially with the compact dust emission from dense cores among the detected lines. These lines also show enhancement in intensities with respect to SiO intensities toward the compact dust emission, suggesting the presence of slow shocks or hot cores in these regions. We find gas temperatures of ≳100 K at 0.1 pc scales based on RADEX modeling of the H 2 CO and NH 3 lines. Although no strong correlations between temperatures and linewidths/H 2 O maser luminosities are found, in high-angular-resolution maps we note several candidate shock-heated regions offset from any dense cores, as well as signatures of localized heating by protostars in several dense cores. Our findings suggest that at 0.1 pc scales in this cloud star formation and strong turbulence may together affect the chemistry and temperature of the molecular gas.